Emerging Conversations in Critical Internationalization Studies - Stein, Sharon; McCartney, Dale M. (Journal of International Students, 2021)
In this paper, we introduce our special issue, “Internationalization for an Uncertain Future: Emerging Conversations in Critical Internationalization Studies.” In addition to reviewing the individual contributions to this issue, we also consider emerging areas of inquiry in the field of critical internationalization studies (CIS), and invite consideration of how the field might responsibly confront the challenges, complexities, and possibilities that emerge in efforts to imagine and practice internationalization otherwise in today’s complex, uncertain, and unequal world.